Failed tubectomy procedures: a retrospective study - Jadhav, Balaji J.; Gomare, Mangala; Chandanshive, Vaishali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: It is difficult to understand the nature of factors leading to failure of sterilization from single institute. Knowing the factors, we can take preventive measures. Those data were of women who filed claims under Family Planning Indemnity Scheme, 2013 (revised 2016). The scheme was not reached at grassroots; therefore, not enough women got the benefit of this scheme. We gave the list of documents as well, which help medical fraternity working in rural area. Methods: Retrospective study of 32 women of failed tubal ligation over a period of four years (from 2016 to 2019). The variables under consideration of study were, parity and age at the time of tubectomy. Time and method of tubectomy. Interval between tubectomy and subsequent pregnancy. Outcome of subsequent pregnancy and further contraceptive acceptance. Descriptive statistics used for frequency analysis. Results: Median age of women was 26 years during tubal sterilization. Seventy two percent women were accepted sterilization on two children. Sixty nine percent of tubal sterilization were performed in puerperium; concurrent with caesarean section and medical termination of pregnancy, while 31% were during interval period. Thirty four percent of women became pregnant within 24 months(2years) of sterilization and cumulative 75% within 60 months (5 years) after sterilization. Sixty nine percent of women had intrauterine pregnancies and 31% ectopic pregnancies. Fifty six percent women accepted medical termination of pregnancy and 53% chosen repeat tubal sterilization. Four women (12%) gave live births. Two of them accepted repeat sterilization and another two intrauterine contraceptive devices. Thirty one percent women had ectopic pregnancy; nine of them came as ruptured ectopic, therefore, exploratory laparotomy with bilateral total salpingectomy were to be performed. Conclusions: Failed tubal sterilization is common when it was performed at younger age and in puerperium. Missed period after sterilization should have high index of suspicion of ectopic pregnancy, which leads to severe maternal morbidity.